Effects of Two Burn Scales on Northern Bobwhite Demographic Parameters and Home Range Size - Shane D. Wellendorf; William E. Palmer (National Quail Symposium Proceedings, 2017)
Properties managed for bobwhite hunting in the Red Hills region use prescribed fire to burn 40-60% of their upland areas annually. Burning large areas could negatively affect bobwhite survival by increasing predation risk. Burning small areas could influence daily habitat use patterns and may influence nesting or brooding processes. Research on how the scale of management influences home range size and demographics of bobwhites is lacking. Therefore, on Tall Timbers Research Station (TTRS) we established 4-140 ha experimental treatment areas and randomly assigned 2 areas to be burned at a small scale (~2.25 ha burn patch size) and 2 areas to be burned at a large scale (~8 ha burn patch size). Upland habitat areas were divided into similar size patches, depending on treatment, with half of the units in the treatment areas burned annually in an alternating pattern. We annually radio-tagged bobwhites (2003-2005) and monitored their survival, productivity, and home range size during the breeding season. In 2003-2004, the risk of mortality was higher on large scale versus small scale treatments during March-May, but there were no differences in 2005. Per capita nest production was higher on small scale areas (0.68 nests/bird) than large scale areas (0.43 nests/bird). Autumn density was higher on small scale treatment areas (3.5 bobwhite/ha, SE = 0.62) compared to large scale treatment areas (2.7 bobwhite/ha SE = 0.67; F1,2 = 12.9, P = 0.07). On TTRS, there were marginal benefits of small scale management for early breeding season survival and productivity, especially during years with high late winter mortality or slow vegetative growth after burning due to drought, but the gains we observed may not be enough to supersede other management priorities.
Keywords: Colinus virginianus; fire; Florida; northern bobwhite; prescribed burning; productivity; scale of management; survival